دور الموالي في حفظ السنة النبوية: آل سيرين نموذجا - عبدالكريم، عثمان بابكر صالح (جامعة أم القرى, 2020)
The Scholars of Hadith took care to show the state narrators, So the books of hadith and men's books were full of news of the narrators and their role in preserving the Prophet's Sunnah. The Moali narrators had a share of this attention because they played a major role in the scientific movement throughout the ages. The description of Almoali did not prevent them from contributing to the scientific renaissance of Muslims. Among them are the Serine family, who have provided vivid examples in the care of preserving the Prophet's Sunnah. The research indicates through extrapolation and analysis, the role of this precious family which presented a group of brothers who were a unique example in preserving the Prophet's Sunnah. Their narrations in the six books were as follows: Mohammed Bin Serine (463 hadiths), Hafsa Bint Serine (85 hadiths), Anas Ben Serine (35 hadiths) and Maabad Ben Serine (8 hadiths).
اعتنى علماء الحديث ببيان أحوال الرواة، فكانت كتب مصطلح الحديث وكتب الرجال حافلة بأخبار الرواة ودورهم في حفظ السنة النبوية، وكان للموالي نصيب من هذه العناية لما قاموا به من دور كبير في الحركة العلمية على مر العصور فلم يمنعهم الوصف من أنهم موالي من الإسهام في النهضة العلمية للمسلمين، ومن هؤلاء الموالي: آل سيرين الذين قدموا نماذج حية في العناية بحفظ السنة النبوية، وقد أبان البحث من خلال الاستقراء والتحليل عن دور هذه الأسرة الكريمة حيث قدمت مجموعة من الإخوة كانوا نموذجا فريدا في حفظ السنة النبوية. وبلغت مروياتهم في الكتب الستة كالتالي: محمد بن سيرين (٤٦٣ حديثا)، حفصة بنت سيرين (٨٥ حديثا)، أنس بن سيرين (35 حديثا)، معبد بن سيرين (8 أحاديث).
Keywords: السنة النبوية -- الموالي -- آل سيرين -- حفظ السنة